Kontribusi Penerapan Motivasi Intrinsik dan Ekstrinsik terhadap Komitmen Organisasi Karyawan Tetap - Lana Fauziyah (BUDGETING : Journal of Business, Management and Accounting, 2022)
This study aims to determine the effect of intrinsic motivation and extrinsic motivation on the organizational commitment of permanent employees at the Bondowoso Regency PDAM office. The research method used is quantitative research. Data collection techniques using observation, interviews and questionnaires to 98 respondents with census techniques. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, and R2 test. The results showed, a) there was a positive and significant effect between intrinsic motivation on organizational commitment with a significance level of 0.000 (p<0.05); b) there is a positive and significant influence between extrinsic motivation on organizational commitment with a significance level of 0.000 (p <0.05). In conclusion, the independent variables (X1, X2) together have a positive and significant effect on the dependent variable (Y) of organizational commitment to permanent employees of the Bondowoso Regency PDAM Office. Keywords: Organizational Commitment, Extrinsic Motivation, Intrinsic Motivation